Antibacterial Activity of Sea Cucumbers Harvested from Karimunjawa - Delianis Pringgenies (Research and Development Center for Marine and Fisheries Product Processing and Biotechnol, 2013)
This research was conducted to discover bioactive compounds in sea cucumbers collected from Karimunjawa as anti-microbial agents against several pathogenic bacteria. Five sea cucumbers species used in this study were Teripang Gamat (Stichopus variegatus), Teripang Nanas (Stichopus chloronotus), Teripang Getah (Bohadschia mamorata), Teripang Emas (Stichopus herrmanni) and Teripang Babi (Bohadschia argus). Sea cucumbers extract were subjected to a series of anti-microbial tests using Staphylococcus aureus, Escherichia coli, Vibrio anguila, Vibrio voinivica, Bacillus subtilis, and Pseudomonas sp. Results showed that in the preliminary study, tissue extract of Bohadschia mamorata and Bohadschia argus were able to suppress the growth of all tested bacteria. Further study used these two sea cucumber extracts, and the results show that Bohadschia mamorata extract at 10 mg/ml showed the largest antibacterial (2.18 mm) towards the pathogenic bacterium Pseudomonas sp., while the smallest antibacterial zone (0.63 mm) was against the growth of Bacillus subtilis. At the concentration level of 20 mg/ml Bohadschia argus extract showed the highest antibacterial zone of 3.68 mm against Staphylococcus aureus and the lowest inhibition zone (1.75 mm) against Pseudomonas sp.